Human factor of The Use Of Robotic Technology In Pediatric neurorehabilitation. (30th September 2020) - Gilardi, F; De Falco, F; Casasanta, D; Andellini, M; Gazzellini, S; Petrarca, M; Castelli, E; Raponi, M; Magnavita, N; Zaffina, S
Abstract: Robotic technology represents a new rehabilitation opportunity that, with an approach similar to a video game, increases the motivation to treat children and seems able to activate brain plasticity, at the basis of the functional recovery due to its interactivity and intensity of the training experience. Literature reports few studies that evaluate the ergonomic aspects of devices for neurorehabilitation, from the point of view of both the operator and the patient. Similar studies in the pediatric field are rare. This study aims to evaluate the response of workers, patients and their parents to this new technology. The study considered the response of the workers (perception of the workload, satisfaction), that of the patients and their parents (expectations, benefits) by comparing the answers to subjective questionnaires of those who made use of the new technology with those who used the traditional technique. Twelve workers, 46 patients and 47 parents were enrolled in the study. Significant differences were recorded in the total workload score of operators who use the robotic technology compared to the traditional therapy (p < 0.001). Patients reported a higher quality of life and satisfaction after the use of robotic neurorehabilitation therapy. The parents of patients undergoing robotic therapy have moderately higher expectations and satisfaction than those undergoing traditional therapy. None of the parameters checked was worse in the new therapeutic technique than in the traditional one. In this pilot study, the robotic neurorehabilitation technique induced an increase in the expectations and satisfaction of patients and their parents. As is frequent in the introduction of new technologies, workers perceived a greater workload. Subsequent studies are needed to verify the results achieved. This study is being developed in an Italian pediatric hospital, with the collaboration and funding of the Italian Ministry of Health, coauthor of this study. Key messages: Robotic therapy presents a higher workload compared to traditional one. Robotic technique induced an increase in quality of life of patients and in expectations and satisfaction of their parents.